Factors associated with anxiety and depression in perimenopausal women with abnormal uterine bleeding: A retrospective cohort study - Jun Hu; Lijuan He (BMC Psychology)
Abstract Objective To investigate factors associated with anxiety and depression in perimenopausal women experiencing abnormal uterine bleeding (AUB), with a focus on endocrine markers and lifestyle factors. Methods This retrospective cohort study analyzed 1,234 perimenopausal women with AUB treated at a tertiary hospital from January 2023 to January 2024. Participants were classified based on DSM-5 diagnoses of anxiety and depression. Data collected included demographics, lifestyle habits, comorbidities, psychiatric history, and endocrine levels (estradiol, follicle-stimulating hormone [FSH], luteinizing hormone [LH], cortisol, prolactin, testosterone, and thyroid-stimulating hormone [TSH]). Logistic regression models identified independent predictors, with interaction and stratified analyses conducted by age group (< 50 and ≥ 50 years). Results Factors associated with anxiety and depression included higher BMI (OR 1.08, P = 0.008), longer AUB duration (OR 1.12, P = 0.001), single/divorced/widowed marital status (OR 1.54, P = 0.015), and lower education levels (OR 1.62, P < 0.001). Smoking history (OR 2.84, P < 0.001) and psychiatric history (OR 3.11, P < 0.001) emerged as strong predictors, while regular exercise was protective (OR 0.64, P = 0.001). Hormonal factors, including lower estradiol and elevated levels of FSH, LH, and cortisol, were significantly linked to increased odds of psychological distress (P < 0.01). Interaction analyses revealed that smoking and elevated cortisol exacerbated risks, whereas regular exercise mitigated the adverse effects of elevated FSH and LH. These associations were consistent across age groups. Conclusions Anxiety and depression in perimenopausal women with AUB are influenced by a combination of demographic, lifestyle, clinical, and endocrine factors. Addressing modifiable risk factors, such as smoking cessation and increased physical activity, may alleviate psychological distress. Further research is needed to elucidate the hormonal pathways connecting endocrine changes to mental health.